Cytoprotective Actions of Omeprazole in Indomethacin – Induced Gastric Mucosal Injury in Rats. - Manna, Mohammed J.; Matloub, Samir Y. N. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Gastric mucosal injury induced by NSAIDs is a major adverse effect of this group of medications, and it is no surprise that protection against such injury has become an important challenge for a better understanding of the mechanisms involved. Materials and methods: This study was conducted on 40 adult male albino rats , divided into 4 groups, the first served as a control received the vehicle , the second received indomethacin orally of 60mg/kg .The third was pretreated 30 minutes prior indomethacin with omeprazole 40mg/kg orally. The fourth was given intraperitoneal L-NAME 20mg/kg plus omeprazole to investigate a possible protective role of nitric oxide. The rats were then sacrificed after 4 hours and their stomachs were isolated and submitted to macroscopical, and microscopical assessment and for the measurement of the gastric prostaglandin E2, myeloperoxidase , and interlukin-4 . Results: Omeprazole pretreatment resulted in a significant decrease (p<0.01) in the gastric damage score. The MPO activity was significantly decreased (p<0.01) , while had no effects on the gastric levels of IL-4 and PGE2. L-NAME given 30 minutes before omeprazole had no influence on the protective effects of omeprazole. Conclusions: The injurious effect of indomethacin can be reduced by omeprazole pretreatment, and that this protective effect of omeprazole may be partly attributed to its antioxidant property reflected by the decrease in the MPO activity.